Governing Differences: Social Diversity, Polycentric Political Economy and Modus Vivendi - Paul Dragos Aligica; Jennifer Brick Murtazashvili (Edward Elgar Publishing, 2025)
This book addresses the crisis in modern governance as a result of increasing value diversity and argues that the ensuing societal and political tensions are most effectively managed using a polycentric political economy and a modus vivendi social philosophy. Expert authors discuss the social fragmentation of modern society, rooted in the expanding diversity of values, beliefs and lifestyles generated by globalization and the technological revolution. Chapters present detailed analysis of a wide range of case studies, including a reassessment of contemporary views, a polycentric political economy through a modus vivendi framework, or the use of blockchain contractualism to reconfigure the building of post-colonial states. They also advocate for a convergence of the institutional theory of polycentricity and the political philosophy of modus vivendi - live and let live - as a basic conceptual framework to uphold a peaceful and tolerant society. This book is a critical resource for students and scholars of political science and public policy in addition to those studying political philosophy, sociology, moral theory or institutional systems. Policymakers and practitioners involved in governance will also find this invaluable due to its timely focus on the tensions generated by pluralism and how they can be alleviated.
Keywords: 320; Governance; Pluralism; Institutionalism; Political Philosophy; Polycentric Political Economy; Coexistence